Self‐determination and a shattered star: Statehood and national identity in the Somali Horn of Africa. Issue 1 (22nd December 2020) - Chonka, Peter; Healy, Sally
Abstract: This article explores the articulation—in different forms, at different periods, and by different actors—of 'national self‐determination' in Somalia and across the Somali‐speaking regions of the Horn of Africa. It explores how this concept can be understood in the context of protracted political fragmentation in Somalia—considering unresolved debates over the ideological foundations of state reconstruction, disagreements about the suitability of federalism, aspirations for the recognition of an independent Republic of Somaliland, and the distinctive trajectory of the Somali Regional State in Ethiopia. Taking a comparative, cross‐border and wide‐angled historical approach, the article argues that ideas of an ethno‐linguistically, culturally and religiously defined Somali 'nation' continue to coexist (and be reproduced, updated and used) within an environment of extreme political fragmentation and across multiple 'state' boundaries. This argument is made through comparative analysis of contemporary examples of the performance of Somali state and nationalist identities within and beyond the region and the distinctive transnational Somali‐language media environment within which these ideas circulate and compete.